Development of an Information Society as a Tool for Improving the Competitiveness of the National Economy - Lebedyeva, Lyudmyla; Poluektova, Nataliya (Regional Barometer. Analyses & Prognoses, 2013)
In modern conditions, competition increases not only at the level of individual enterprises but also at the level of regions, countries and groups of countries. The problems of competitive states are insufficiently studied. This paper focuses on the problems of search tools to enhance national competitiveness through the analysis of the factors of information society development. The work consisted in identifying factors of informatization that have not been taken into calculating the indices of competitiveness in the data of the World Economic Forum. Next, the correlation coefficients between the identified factors of informatization and the main indices of competitiveness were calculated. This reveals the most significant dependencies and provides a basis for recommendations for the use of these instruments for some countries. As an example the main directions of improving competitiveness by improving factors for informatization of Ukraine and Poland were formulated.